2013
DOI: 10.1155/2013/595318
|View full text |Cite
|
Sign up to set email alerts
|

First-Year Outcomes after Stroke Rehabilitation: A Multicenter Study in Thailand

Abstract: Stroke affects the long-term quality of life and the well-being of patients and families. Stroke patients gain benefits from rehabilitation. Authors reported 1-year outcomes of stroke rehabilitation in 327 patients registered to the Thai Stroke Rehabilitation Registry. The outcomes included death rate, readmission rate, functional ability score (Barthel Index, BI), and factors affecting BI score. Of 327 patients, 214 (65.4%) had adequate follow-up data for analysis. The average age was 62.1 ± 12.5 years, and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…17 Our results are in contrast against those in a study by Kuptniratsaikul, et al who reported that 51.5% of patients had improved functional level while 12.8% saw a decline one year post-stroke. 18 These studies confirm the natural course of functional recovery in which significant improvement occurs within 6-12 months, with a subsequent observed tendency of the patient's functional level to stabilize or decline thereafter. It is important to emphasize that in addition to our study which enrolled stroke patients (25.4%), we also enrolled patients with SCI (53.3%) and TBI (3.5%).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…17 Our results are in contrast against those in a study by Kuptniratsaikul, et al who reported that 51.5% of patients had improved functional level while 12.8% saw a decline one year post-stroke. 18 These studies confirm the natural course of functional recovery in which significant improvement occurs within 6-12 months, with a subsequent observed tendency of the patient's functional level to stabilize or decline thereafter. It is important to emphasize that in addition to our study which enrolled stroke patients (25.4%), we also enrolled patients with SCI (53.3%) and TBI (3.5%).…”
Section: Discussionsupporting
confidence: 80%
“…Other studies reported the fact that depression is an independent indicator of poor functional status in the long-run. 18,25,26 Concerning complications, Rinkaewkan and Kuptniratsaikul conducted a retrospective study in 201 SCI patients admitted to rehabilitation wards between 2006-2010. They found an absence of comorbidity and the ability to undertake an intensive rehabilitation program to be associated with increased functional score after rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Only 214 patients (65.4%) could be followed up for at least one year, whereas 8 (2.4%) died, 3 withdrew and 102 lost to follow up. Concerning the severity of participants evaluated by BI, 42.8% was mild, 17.9% moderately, 13.8% severely to very severely disabled and only 25.5% was independently [15]. The baseline characteristics of 214 patients are presented in Table  1.…”
Section: Resultsmentioning
confidence: 99%
“…Previous longitudinal investigations of cerebral activity and/or cerebral regulation have been limited to two (the majority of studies) or three separate observations [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Epidemiological studies have suggested that the greatest amount of recovery occurs during the first 3 months after stroke onset [ 15 ].…”
Section: Introductionmentioning
confidence: 99%